DOES THE EXPLOITATION OF THE DAMOUS WADI AQUIFER MAKE IT VULNERABLE TO MARINE INTRUSION? - HALLOUCHE, Ouassila; YAMEOGO , Missom Gontran Armel (GeoScience Engineering, 2024)
The Damous wadi aquifer in the coastal city of Tipaza in Algeria provides the town of Damous with potable water as well as the irrigation of the crops grown in the valley. In order to see the effect of this exploitation on the level of the water table, we measured during five campaigns the depth at which the water is fond in seven wells. Four of these wells are located near the sea, one far from it and two intermediate wells. We also measured other parameters such as a conductivity and the level of chlorides in the water from these wells to see if the groundwater is polluted by seawater. The results obtained showed that the water is 3 m or 4 m away except for the well farthest from the sea where the water is more than 6 m away. For wells close to the sea, the conductivity reaches for some 3000 μS/cm and the chlorides concentration 300 mg/l. These results remain consistent with Algerian standards. The Damous wadi aquifer seems to resist the marine intrusion to which it is sometimes subject thanks to the good rainfall and the releases from the Kef Eddir dam from which it benefits.